Long‐term safety and sustained efficacy of extended‐release pramipexole in early and advanced Parkinson's disease. (4th February 2014) - Hauser, R. A.; Schapira, A. H. V.; Barone, P.; Mizuno, Y.; Rascol, O.; Busse, M.; Debieuvre, C.; Fraessdorf, M.; Poewe, W.; ,
<x xml:space="preserve">Abstract</x> Background and purpose To assess the long‐term safety and efficacy of pramipexole as a once‐daily (q.d.) extended‐release oral formulation in early or advanced Parkinson's disease (PD). Methods In two double‐blind (DB) studies of early PD and one of advanced PD, active‐treatment arms received pramipexole immediate release (IR) or extended release (ER), with exposure lasting up to 33 weeks. In open‐label (OL) extensions that followed immediately, subjects took ER q.d. for up to 80 weeks, with dosage adjustment permitted (range 0.375–4.5 mg q.d.). Results Of 590 subjects completing an early‐PD DB study, 511 entered the early‐PD OL extension; 408 completed it. Reported adverse events (AEs) with incidence ≥10.0% were somnolence (15.1%), peripheral edema (11.7%) and back pain (10.6%). Of 465 subjects completing the advanced‐PD DB study, 391 entered the advanced‐PD OL extension; 329 completed it. Reported AEs with incidence ≥10.0% were dyskinesia (27.4%) and somnolence (13.6%). Impulse control disorders were identified by semi‐structured interview in 13 subjects (1.4% of 902). In exploratory analyses, adjusted mean Unified Parkinson's Disease Rating Scale (UPDRS) Parts II + III scores (excluding ex‐placebo recipients) remained substantially improved from DB baseline scores prior to pramipexole introduction, at −6.6 and −6.3 points amongst ex‐DB‐ER and ex‐DB‐IR recipients after 113 weeks of pramipexole (33 DB plus 80 OL) in early PD, and −11.5 and −9.1 after up to 113 weeks (up to 33 DB plus 80 OL) in advanced PD. Conclusions These results support the long‐term safety and efficacy of pramipexole ER in early and advanced PD. AEs were typical for dopaminergic medications, and UPDRS scores suggested sustained symptomatic benefit.